Spatiotemporal dynamics of microplastics, mesoplastics and macrolitter in Cypriot shores: An integrated size assessment to discern transport pathways - Ioannis Savva; Dror L. Angel (Journal of Environmental Chemical Engineering, 2026)

Into the Wild: Farm‐Derived Energy and Nutrients Enter Marine Food Webs With Carrying Capacity Implications for Aquaculture Management - Myriam D. Callier; Ramon Filgueira; Carrie J. Byron; Daniele Brigolin; Dror L. Angel; Sophie J. I. Koch; Bobbi Hudson; Frank Kane; Heather Moore; Antonio Agüera; Lotta C. Kluger; Christopher W. McKindsey (Reviews in Aquaculture, 2026)
Marine aquaculture is expanding globally, yet its interactions with surrounding ecosystems remain complex and insufficiently understood. This study reviews the fluxes of energy and nutrients from three major aquaculture systems: finfish cages, suspended bivalves, and seaweed farms and considers their implications for ecosystem functioning and management under the ecosystem approach to aquaculture (EAA). Using a focused literature review and expert input from International Council for the Exploration of the Sea (ICES), Working Group on Ecological Carrying Capacity of Aquaculture (ICES WGECCA), we synthesized data on farm‐derived fluxes, trophic transfers, and ecological consequences. From this synthesis, we developed three conceptual models illustrating direct and indirect pathways of energy and nutrient exchange between farms and marine food webs. Seven case studies from temperate and subtropical systems were analyzed to exemplify site‐specific effects, including organic enrichment, altered benthic‐pelagic coupling, and changes in wild species assemblages. Key findings highlight that fed aquaculture (finfish) releases substantial particulate and dissolved waste, influencing benthic geochemistry, while extractive systems (bivalves, seaweeds) modulate nutrient cycling. Integrated multi‐trophic aquaculture (IMTA) offers the potential for synergistic flux recycling within the farm system. Wild mobile fauna attracted to farm systems shelter and feed directly on the farmed product, fouling, or particulate wastes and dislodgements from the farm, thereby strengthening farm‐environment coupling. These insights underscore the need for adaptive management and carrying capacity (CC) assessments that account for energy‐nutrient fluxes to ensure sustainable aquaculture development aligned with EAA principles.

The untold story of Sea Caves: Lost and found anthropogenic debris in confined marine environments - Ioannis Savva; Leda L. Cai; Melina Marcou; Dror Angel (Marine Pollution Bulletin, 2026)

Identifying a sustainable operating window for seaweed aquaculture in the Global North: balancing expansion barriers and carrying capacity - Sophie J.I. Koch; Ramon Filgueira; Jóhanna Alberg; Dror L. Angel; Carrie J. Byron; Mariana Cerca; Leeann B. Ennis; Urd Grandorf Bak; Frank Kane; Jonne Kotta; Stefan Kraan; Myron Peck; et al. (Aquaculture, 2026)

Citizen science-based jellyfish observation initiatives in the Mediterranean Sea - Dor Edelist; Antonio Canepa-Oneto; Joel Azzopardi; Ainara Ballesteros; Jesús Bellido; Ferdinando Boero; Cesar Bordehore; Alan Deidun; Eva S. Fonfría; Adam Gauci; Josep Maria Gili; Sonia K. M. Gueroun; et al. (Hydrobiologia, 2025)
We present Citizen Science-based Jellyfish Observation Initiatives (CS JOIs) across the Mediterranean Basin and propose a path toward standardization of the data they produce. We explored data collection and management through a shared database schema. Using an expert opinion questionnaire and adhering to standards that are recognized globally (e.g., by GBIF, OBIS, and EMODnet) such as Darwin Core and IOOS terminology, we propose a three-stage approach toward data management and standardization. JOIs vary in purpose, function, language, data collection, validation methodology, outreach, and levels of citizen engagement and training. This diversity presents unique opportunities and challenges for data collection and management. JOIs typically combine the dual role of providing real-time alert systems and enhancing our long-term knowledge of jellyfish distribution and, eventually, ecology. When global reporting systems are considered, local initiative identity, language, purpose, and community must be preserved to allow meaningful CS processes to evolve, while the integration of JOIs within them (and data collection and management in general) must be performed via standardized and shared methodologies. Finally, we discuss the contribution of novel technologies toward improving the activities and management of JOIs worldwide.

Substrate preferences and the effect of temperature on planulae settlement of the scyphozoan Rhopilema nomadica - Hila Dror; Dror L. Angel (Hydrobiologia, 2025)
Rhopilema nomadica is the most prominent jellyfish species in the eastern Mediterranean, forming huge annual summer swarms. Although planula settlement success is essential in the formation of jellyfish outbreaks, quantitative studies to examine its response to environmental variables have not been performed thus far due to the difficulty in collecting planulae. We concentrated large numbers of R. nomadica planulae to study the effect of substrate type and seawater temperature on planula settlement. In the substrate preferences experiment, two natural substrates (bivalve shells and kurkar rock) and two artificial substrates (concrete and plastic (PVC)) were offered for planula settlement. Settlement success was not different between concrete, PVC, and kurkar substrates, but was significantly lower on the shells. In the temperature experiment, planulae were able to settle and metamorphose into polyps at all five temperatures (16—32 °C) tested, on glass slides, and most settled within three days. Higher temperatures were not only associated with accelerated settlement but also increased settlement success. The anticipated increase in marine infrastructures (potential settlement substrates), and rising seawater temperatures may favor planula settlement success and further enhance outbreaks of R. nomadica in the Mediterranean.

Rhizostoma pulmo (Scyphozoa; Rhizostomeae) planulae and polyps: production, settlement preferences and development - Marie Meffre; Anaïs Courtet; Zafrir Kuplik; Hila Dror; Dror Angel; Etienne Bourgouin; Juan-Carlos Molinero; Delphine Bonnet (Marine Biology, 2025)

Indicators for ecological carrying capacity of bivalve and seaweed aquaculture - Carrie J. Byron; Sophie J. I. Koch; Myriam D. Callier; Lotta Kluger; Dror L. Angel; Jan Vanaverbeke; Ramon Filgueira (Reviews in Aquaculture, 2024)
Within the framework of Ecosystem Approach to Aquaculture (EAA), ecological carrying capacity (ECC) is a key concept that helps to determine the upper limit of production without compromising ecosystem functioning. The implementation of ECC is complex as ECC differs between type of farms and location and standardised methods should be developed for management. There is therefore a clear need for operational indicators. The objectives of this paper were: (1) to carry out a systematic literature review on shellfish and seaweed aquaculture‐environment interactions to list the most used environmental indicators, (2) to classify the indicators according to the effects they measure (i.e., benthic, water quality, food web interactions, cultured organism health, resource use) and the scale at which they are applied, and (3) to assess their potential based on four indicator criteria categories: sensitivity, accuracy and precision, feasibility and utility, and ecosystem‐level scalability. Overall, indicators describing benthic effects were the most highly cited and scored. Indicators identified for bivalve and seaweed culture were discussed and compared to previous work on salmon aquaculture indicators to highlight similarities and differences across trophic levels. In addition, questions related to the challenges of ECC indicators implementation were presented to a panel of experts. The scoring and consultation provided the source of discussion on environmental management consistent with EAA.

Monitoring jellyfish outbreaks along Israel's Mediterranean coast using digital footprints - Tal Levy; Andrea Ghermandi; Yoav Lehahn; Dor Edelist; Dror L. Angel (Science of The Total Environment, 2024)

Jellyfish sting web survey: clinical characteristics and management of Rhopilema nomadica envenomation in the Mediterranean Sea - Dor Edelist; Dror L. Angel; Nitza Barkan; Carmel Danino-Gozlan; Ana Palanker; Limor Barak; Emily Robertson; Yedidia Bentur (Regional Environmental Change, 2023)

Ecological carrying capacity in mariculture: Consideration and application in geographic strategies and policy - Jeffrey Fisher; Dror Angel; Myriam Callier; Daniel Cheney; Ramon Filgueira; Bobbi Hudson; Christopher W. McKindsey; Lisa Milke; Heather Moore; Francis O’Beirn; Jack O’Carroll; Berit Rabe; et al. (Marine Policy, 2023)

Mechanism of nanoplastics capture by jellyfish mucin and its potential as a sustainable water treatment technology - Eric A. Ben-David; Maryana Habibi; Elias Haddad; Marei Sammar; Dror L. Angel; Hila Dror; Haim Lahovitski; Andy M. Booth; Isam Sabbah (Science of The Total Environment, 2023)

Tracking Jellyfish Swarm Origins Using a Combined Oceanographic-Genetic-Citizen Science Approach - Dor Edelist; Øyvind Knutsen; Ingrid Ellingsen; Sanna Majaneva; Nicole Aberle; Hila Dror; Dror L. Angel (Frontiers in Marine Science, 2022)
Biological invasions of jellyfish may critically affect ecosystems and ecosystem services, yet their complex life cycle makes tracking their origins and dispersal vectors a challenging task. Here we combine citizen science observations, oceanographic modeling, and population genetics to track swarms of the invasive nomad jellyfish, Rhopilema nomadica , across the Eastern Mediterranean Sea. Jellyfish observations were recorded by citizens from two Israeli beaches in two consecutive years. A Lagrangian model coupled with a high-resolution 3D hydrodynamic model (SINMOD) was then used to simulate drift of ephyrae from probable polyp bed locations. Finally, mitochondrial DNA (mtDNA) sequence was constructed to examine swarm connectivity. Temporal (both seasonal and interannual) variation in observed swarms generally exceeded spatial differences between the two surveyed beaches. Early detection of swarms by citizens in offshore waters and the higher offshore particle distribution shown by the drift model, point to considerable offshore transport of the swarms. However, a higher probability was found for a nearshore location of the polyp beds, as nearshore origins were more closely correlated to hits on target beaches. R. nomadica released as ephyrae in early spring were likely to reach target beaches 200-300 km down current within two to three months as swarms of young adults in the early summer bathing season. R. nomadica populations exhibited little temporal or spatial genetic differentiation, a typical feature of a species that has recently undergone rapid population expansion. The offshore transport, the lack of genetic structure, and the interannual differences in both hydrodynamics and citizen scientist observations, all indicate decentralized swarm origins. This type of interdisciplinary approach can thus provide viable tools to track bloom formations. Understanding the complexity of jellyfish swarm dynamics supports future management strategies such as forecasting, preparedness and public education.

Is aquaponics good for the environment?—evaluation of environmental impact through life cycle assessment studies on aquaponics systems - Asael Greenfeld; Nir Becker; Janet F. Bornman; Sabrina Spatari; Dror L. Angel (Aquaculture International, 2022)

Nitrification Activity of the Sponge Chondrosia reniformis Under Elevated Concentrations of Ammonium - Philip Nemoy; Ehud Spanier; Dror L. Angel (Frontiers in Marine Science, 2021)
This study examined the ability of a Mediterranean demosponge Chondrosia reniformis to oxidize exogenous ammonium, simulating N-rich conditions that occur near finfish farms. We hypothesized that as the concentration of ammonium increases in the surrounding seawater, nitrification mediated by microbes associated with C. reniformis will lead to enhancement of ammonium uptake, nitrate excretion and oxygen consumption by the sponge holobiont. To test this hypothesis, we conducted laboratory experiments with C. reniformis explants exposed to ammonium enrichments (300–6667 nM) and to ambient seawater (45–1511 nM ammonium). We analyzed inhaled (IN) and exhaled (EX) water samples for dissolved oxygen, ammonium, nitrates and retention of picoplankton cells. We observed ammonium uptake in nearly half the cases and excretion of nitrate in most experimental outcomes. Yet, the consumption of ammonium and oxygen, as well as the excretion of nitrate by C. reniformis were not related to the concentration of inhaled ammonium, which suggests that the nitrification activity of sponge-associated microbes is not necessarily related to the concentration of ammonium in the surrounding seawater. Further research is required to reveal the sources of nitrate released from sponges and the fate of this nitrate in natural and manipulated ecosystems.

Nitrate-Enrichment Structures Phytoplankton Communities in the Shallow Eastern Mediterranean Coastal Waters - Eyal Rahav; Ofrat Raveh; Keren Yanuka-Golub; Natalia Belkin; Peleg Astrahan; Meor Maayani; Noam Tsumi; Yael Kiro; Barak Herut; Jacob Silverman; Dror L. Angel (Frontiers in Marine Science, 2020)
Submarine groundwater discharge (SGD) has been shown to be an important source of nutrients in coastal environments, especially nitrogen and silica, and thereby relive nutrient limitation to phytoplankton. Here, we followed autotrophic microbial biomass, activity, and community composition at a site strongly influenced by SGD and a nearby nutrients-poor reference site at the oligotrophic Israeli shallow rocky coast [southeastern Mediterranean Sea (SEMS)] between 2011 and 2019. The surface water at the SGD-affected area had significantly higher NO 3 + NO 2 (∼10-fold) and Si(OH) 4 (∼2-fold) levels compared to the reference site, while no significant differences were observed for PO 4 or NH 4 . This resulted in a significant increase in algae biomass (∼3.5-fold), which was attributed to elevated Synechococcus (∼3.5-fold) and picoeukaryotes (∼2-fold) at the SGD-affected site, and in elevated primary production rates (∼2.5-fold). Contrary to most SGD-affected coastal areas, diatoms biomass remained unchanged between sites, despite the elevated N and Si, suggesting the dominance of picophytoplankton over microphytoplankton at the SEMS. DNA sequencing of the 16S and 18S rDNA supported these findings. These results highlight the influence of SGD on shallow-water microbial populations. Our observations are consistent with recent studies showing that phytoplankton along the Israeli coast are likely nitrogen + silica limited, and may have important ecological and regulatory implications for environmental policy and management of coastal aquifers.

Identifying knowledge levels of aquaponics adopters - Asael Greenfeld; Nir Becker; Janet F. Bornman; Dror L. Angel (Environmental Science and Pollution Research, 2020)

New Mediterranean Biodiversity Records 2019 - BRANCO DRAGIČEVIĆ; OLGA ANADOLI; DROR ANGEL; MOULOUD BENABDI; GHAZI BITAR; LUCA CASTRIOTA; FABIO CROCETTA; ALAN DEIDUN; JAKOV DULČIĆ; DOR EDELIST; VASILIS GEROVASILEIOU; SALVATORE GIACOBBE; et al. (Mediterranean Marine Science, 2019)
This paper is a collection of novel distributional records of 20 species belonging to 8 phyla (Chlorophyta, Rhodophyta, Cnidaria, Ctenophora, Annelida, Mollusca, Arthropoda and Chordata) from 11 Mediterranean countries, namely, Spain: an additional record of the Canary dentex Dentex canariensis is reported from Spain (Valencia), this is the northernmost record of this species in the Mediterranean; Algeria: the first documented record of Caulerpa chemnitzia is reported from the Algerian coast; France: the first record of the Spotted sea hare Aplysia dactylomela is reported from the eastern coast of Corsica; Italy: the first records of the Lessepsian polychaete Dorvillea similis and the alien bivalve Isognomon legumen are reported from Italian waters while additional records of Mnemiopsis leidyi in the south Adriatic are provided; Libya: the first record of an alien mollusc Crepidula fornicata is reported from Libyan waters; Malta: multiple sightings of gelatinous species Apolemia uvaria, Phacellophora camtschatica and Physophora hydrostatica are reported for the first time from Maltese waters, as well as the first tentative record of the Orange-spotted grouper Epinephelus cfr. coioides; Greece: an occurrence of a rare Bigeye thresher shark Alopias superciliosus is reported from Hellenic Ionian waters, while the first records of the alien Mertens’ prawn-goby Vanderhorstia mertensi, the recently described cyclopoid copepod Oithona davisae and the alien red seaweed Asparagopsis armata are reported from the Aegean Sea. The presence of the micromollusc Euthymella colzumensis is confirmed for Greece; Cyprus: the first record of the red cornetfish Fistularia petimba is reported from Cyprus; Turkey: the first record of the alien jellyfish Marivagia stellata is reported from south-eastern Turkey; Israel: the first records of the sea nettle Chrysaora sp. in the Levant are reported.

Benthic macro-faunal abundance and diversity and sediment distribution in Akhziv submarine canyon and the adjacent slope (eastern Levant Basin, Mediterranean Sea) - MIA RODITI-ELASAR; DAN KEREM; MICHAEL LAZAR; ORIT BARNEAH; AHUVA ALMOGI-LABIN; DROR L. ANGEL (Mediterranean Marine Science, 2019)
The Israeli coastline is generally characterized by a broad and shallow continental shelf. Akhziv submarine canyon (ASC), in its northern reach, creates a locally unique marine ecosystem. The present study is the first to investigate the benthic macro-fauna of ASC, in order to assess its importance as a potential productivity ‘hotspot’ within its ultra-oligotrophic surroundings. Seven research cruises were conducted during 2010-2013, along ASC’s two channels and at iso-bathic control sites on the adjacent slope (AS), encompassing 8 sampling stations, at depths of 40-450 m. Bottom samples were collected by a Van Veen Grab, gravity corer and a GOMEX box corer. The infauna (≥500 µm) were counted and identified to the lowest possible taxonomic level. Sediments were analysed for grain size & composition and total organic carbon concentration. Mean benthic macro-faunal abundance (individuals/500ml ± SD) was higher inside the canyon (13.0±19.4) compared to the AS (2.9±3.3) (p=0.004), as was estimated true taxon richness (Chao1): 42.2 versus 10, respectively. Sediments’ mode grain size was found to be significantly higher in ASC’s eastern channel compared to AS (p=0.028), along with sand enrichment of up to 36%. The higher macrofaunal abundance and taxon richness may relate to a more heterogeneous sea bed provided by the higher diversity in grain size existing inside ASC. A relatively rich benthic realm, such as that observed in the ASC, may serve as a refuge for certain species and by hosting a relatively diverse assemblage, stands a better chance of adapting to changing conditions such as climate change.

Ocean current connectivity propelling the secondary spread of a marine invasive comb jelly across western Eurasia - Cornelia Jaspers; Bastian Huwer; Elvire Antajan; Aino Hosia; Hans‐Harald Hinrichsen; Arne Biastoch; Dror Angel; Ragnhild Asmus; Christina Augustin; Siamak Bagheri; Steven E. Beggs; Thorsten J. S. Balsby; et al. (Global Ecology and Biogeography, 2018)
Aim Invasive species are of increasing global concern. Nevertheless, the mechanisms driving further distribution after the initial establishment of non‐native species remain largely unresolved, especially in marine systems. Ocean currents can be a major driver governing range occupancy, but this has not been accounted for in most invasion ecology studies so far. We investigate how well initial establishment areas are interconnected to later occupancy regions to test for the potential role of ocean currents driving secondary spread dynamics in order to infer invasion corridors and the source–sink dynamics of a non‐native holoplanktonic biological probe species on a continental scale. Location Western Eurasia. Time period 1980s–2016. Major taxa studied ‘Comb jelly’ Mnemiopsis leidyi . Methods Based on 12,400 geo‐referenced occurrence data, we reconstruct the invasion history of M. leidyi in western Eurasia. We model ocean currents and calculate their stability to match the temporal and spatial spread dynamics with large‐scale connectivity patterns via ocean currents. Additionally, genetic markers are used to test the predicted connectivity between subpopulations. Results Ocean currents can explain secondary spread dynamics, matching observed range expansions and the timing of first occurrence of our holoplanktonic non‐native biological probe species, leading to invasion corridors in western Eurasia. In northern Europe, regional extinctions after cold winters were followed by rapid recolonizations at a speed of up to 2,000 km per season. Source areas hosting year‐round populations in highly interconnected regions can re‐seed genotypes over large distances after local extinctions. Main conclusions Although the release of ballast water from container ships may contribute to the dispersal of non‐native species, our results highlight the importance of ocean currents driving secondary spread dynamics. Highly interconnected areas hosting invasive species are crucial for secondary spread dynamics on a continental scale. Invasion risk assessments should consider large‐scale connectivity patterns and the potential source regions of non‐native marine species.

State of the Art and Challenges for Offshore Integrated Multi-Trophic Aquaculture (IMTA) - Bela H. Buck; Max F. Troell; Gesche Krause; Dror L. Angel; Britta Grote; Thierry Chopin (Frontiers in Marine Science, 2018)

Local perspectives on regional challenges: jellyfish proliferation and fish stock management along the Israeli Mediterranean coast - Dror L. Angel; Dor Edelist; Shirra Freeman (Regional Environmental Change, 2016)

The elusive nature of fluorescent organic matter in Lake Kinneret, Israel - Jonathan Liberzon; Yohay Carmel; Dror L. Angel (Hydrobiologia, 2016)

Impacts of climate change on biodiversity in Israel: an expert assessment approach - Marcelo Sternberg; Ofri Gabay; Dror Angel; Orit Barneah; Sarig Gafny; Avital Gasith; José M. Grünzweig; Yaron Hershkovitz; Alvaro Israel; Dana Milstein; Gil Rilov; Yosef Steinberger; et al. (Regional Environmental Change, 2015)

The impact of climate change on mediterranean intertidal communities: losses in coastal ecosystem integrity and services - Gianluca Sarà; Martina Milanese; Ivana Prusina; Antonio Sarà; Dror L. Angel; Branko Glamuzina; Tali Nitzan; Shirra Freeman; Alessandro Rinaldi; Valeria Palmeri; Valeria Montalto; Marco Lo Martire; et al. (Regional Environmental Change, 2014)

Blooms of the invasive ctenophore, Mnemiopsis leidyi, span the Mediterranean Sea in 2009 - Verónica L. Fuentes; Dror L. Angel; Keith M. Bayha; Dacha Atienza; Dor Edelist; Cesar Bordehore; Josep-Maria Gili; Jennifer E. Purcell (Hydrobiologia, 2010)

Preface - Jennifer E. Purcell; Dror Angel (Hydrobiologia, 2010)

δ15N as a natural tracer of particulate nitrogen effluents released from marine aquaculture - Sonja Lojen; Ehud Spanier; Anat Tsemel; Timor Katz; Noa Eden; Dror L. Angel (Marine Biology, 2005)

In situ biofiltration: a means to limit the dispersal of effluents from marine finfish cage aquaculture - Dror L. Angel; Noa Eden; Stephen Breitstein; Amir Yurman; Timor Katz; Ehud Spanier (Hydrobiologia, 2002)